Layered double hydroxide‐based photocatalytic materials toward renewable solar fuels production - Xuanang Bian; Shuai Zhang; Yunxuan Zhao; Run Shi; Tierui Zhang (InfoMat, 2021)
Abstract Photocatalysis is an ideal and promising green technology to drive numerous chemical reactions for valued chemicals production under very mild conditions, thereby providing solutions to global energy and environment issues related to burning fossil fuels. Over the past decade, layered double hydroxides (LDHs), as the members in two‐dimensional materials family, have attracted much attention due to their many advantages in photocatalysis, such as facile synthesis, low cost and powerful tunability of composition. In this review, we provide a synthetic overview of recent research advances of LDH‐based photocatalysts, with the main discussion of the design strategies to improve their photocatalytic performance, including component control, defect engineering, hybridization, and topological transformation. Structure‐performance correlations and tailor‐made material synthesis strategies are elaborated to discuss how to realize high‐performance LDH‐based photocatalysts for three important reactions (i.e., water splitting, CO2 conversion, and N2 reduction) to generate desirable solar fuels. Further, the remaining challenges and future perspectives of LDH‐based photocatalysts are summed up, aiming to inspire brand new solutions for pushing forward the development of LDH‐based photocatalysis.